2010
DOI: 10.1186/1471-2164-11-611
|View full text |Cite
|
Sign up to set email alerts
|

The genomic underpinnings of apoptosis in the silkworm, Bombyx mori

Abstract: BackgroundApoptosis is regulated in an orderly fashion by a series of genes, and has a crucial role in important physiological processes such as growth development, immunological response and so on. Recently, substantial studies have been undertaken on apoptosis in model animals including humans, fruit flies, and the nematode. However, the lack of genomic data for silkworms limits their usefulness in apoptosis studies, despite the advantages of silkworm as a representative of Lepidoptera and an effective model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 76 publications
3
67
0
Order By: Relevance
“…Primers for qRT-PCR were designed according to the sequences of the target genes ( Table 2). In detail, we evaluated the expression of autophagy-related genes BmATG5 (GenBank accession number NM_001142487), BmATG6 (NM_0011 42490) and BmATG8 (NM_001046779) [32,60] and apoptosis-related genes BmICE-2 (DQ360829), BmCaspase-4 (HQ456874) and BmIAP (NM_001043559) [61,62].…”
Section: Tunel Assaymentioning
confidence: 99%
“…Primers for qRT-PCR were designed according to the sequences of the target genes ( Table 2). In detail, we evaluated the expression of autophagy-related genes BmATG5 (GenBank accession number NM_001142487), BmATG6 (NM_0011 42490) and BmATG8 (NM_001046779) [32,60] and apoptosis-related genes BmICE-2 (DQ360829), BmCaspase-4 (HQ456874) and BmIAP (NM_001043559) [61,62].…”
Section: Tunel Assaymentioning
confidence: 99%
“…Recently cDNA of Bmp53 was examined in B. mori larvae and cells and these studies suggested that Bmp53 mRNA levels were elevated after UV irradiation and actinomycin D treatment (Zhang et al, 2011).…”
Section: Characterization Of Sfp53 Apoptotic Activitymentioning
confidence: 99%
“…Dronc plays a critical role in developmental and stress-induced apoptotic cell death in Drosophila, by activating the effector caspase DrICE (Hay and Guo, 2006;Cooper et al, 2009;Kumar and Doumanis, 2000). In lepidopteran insects, while effector caspases have been identified from several insects, including S. frugiperda, Trichoplusia ni and Spodoptera littoralis (Ahmad et al, 1997;Hebert et al, 2009;Liu et al, 2005), initiator caspases have not been characterized, although their presence has been suggested in S. frugiperda and Bombyx mori cells (Manji and Friesen, 2001;Huang et al, 2001;LaCount et al, 2000;Tanaka et al, 2008;Zhang et al, 2010;Zoog et al, 2002).…”
Section: Introductionmentioning
confidence: 97%